2020
DOI: 10.1016/j.foreco.2020.118337
|View full text |Cite
|
Sign up to set email alerts
|

Forest composition, fuel loading, and soil chemistry resulting from 50 years of forest management and natural disturbance in two southeastern Coastal Plain watersheds, USA

Abstract: Globally, prescribed fire, harvesting, and understory mastication, alone and in combination, are common forest management practices. Timber commodities, wildlife habitat, wildfire fuel reduction, soil conservation, and water quality are frequently targeted and assessed as these practices are utilized. In the 1960s, a study of paired, first-order watersheds was established in coastal South Carolina, USA, to evaluate the long-term impacts of forest management (i.e. prescribed fire, thinning, mastication of under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…This system is quite similar to the fuel types of coniferous, deciduous, mixed wood, slash, and open grassland, as defined in the Canadian Fire Behavior Prediction System (FBPS) [36]. Various research has demonstrated the feasibility of integrating ALS and optical images to map the fuel types (alternatively fuel models), such as the ones defined by the Northern Forest Fire Laboratory (NFFL) [36,41,49,50,60,61]. The proposed algorithm for mapping the surface fuel load is therefore most likely able to substitute the fuel types of the FBPS, NFFL, and NFDRS classification systems to moderately improve the mapping performance for forests with undulating terrain morphology in mountainous area.…”
Section: An Examination Of the Appropriateness Of The Cokriging-based Surface Fuel Mapping Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…This system is quite similar to the fuel types of coniferous, deciduous, mixed wood, slash, and open grassland, as defined in the Canadian Fire Behavior Prediction System (FBPS) [36]. Various research has demonstrated the feasibility of integrating ALS and optical images to map the fuel types (alternatively fuel models), such as the ones defined by the Northern Forest Fire Laboratory (NFFL) [36,41,49,50,60,61]. The proposed algorithm for mapping the surface fuel load is therefore most likely able to substitute the fuel types of the FBPS, NFFL, and NFDRS classification systems to moderately improve the mapping performance for forests with undulating terrain morphology in mountainous area.…”
Section: An Examination Of the Appropriateness Of The Cokriging-based Surface Fuel Mapping Methodsmentioning
confidence: 97%
“…Surface fuel loads and bulk density are primarily subject to forest structures related to species composition, phenology, and canopy height [41,[46][47][48][49][50]. Distribution of surface fuel loads is therefore a consequence of the interaction of multiple factors such as forest type or overstorey/understorey species, topographic relief, and climate.…”
Section: Introductionmentioning
confidence: 99%
“…Litter (Oi Horizon), duff (Oe + Oa Horizons), and woody fuel depth (defined as the length from the top of the Oi horizon to the top of a down and dead woody fuel particle lying along a planar transect) were measured at 3.7, 7.6, and 12 m along each linear transect. Additionally, litter and duff were destructively sampled within a 0.09 m 2 PVC plastic frame to determine the O Horizon load (Coates et al 2020). Along each transect, one sample was collected at the end of the 120 • and 240 • transects and one sample was collected within 1.5 m of the origin for the 0 • transect.…”
Section: Study Design and Field Measurementsmentioning
confidence: 99%
“…Some management objectives, such as wildlife habitat management and hazardous fuel reduction, for example, necessitate different forest structures and species compositions [15,27]. Altered fire regimes, that may include more frequent and persistent prescribed fire ignitions to achieve desired management goals, may directly affect organisms as a primary soil-forming factor [28,29]. Therefore, soil chemical properties may also be altered as a product of management intent [29].…”
Section: Temporal and Spatial Variability Of Soil Properties And Fire Effectsmentioning
confidence: 99%
“…Altered fire regimes, that may include more frequent and persistent prescribed fire ignitions to achieve desired management goals, may directly affect organisms as a primary soil-forming factor [28,29]. Therefore, soil chemical properties may also be altered as a product of management intent [29]. Furthermore, atmospheric N deposition and N saturation in some geographic locations may actually hamper management objectives because anthropogenic N enrichment may stifle any potential competitive advantages pyrophytic vegetation exhibit [15][16][17][18]25,26].…”
Section: Temporal and Spatial Variability Of Soil Properties And Fire Effectsmentioning
confidence: 99%